Extensão popular e educação popular : práticas educativas para descolonização da extensão universitária - Santos, José Ledy Carvalho (2023)
The present study analyzes the Popular Extension in the university, taking as assumptions the educational practices of Popular Education within the scope of the University Extension, observing the actions developed by the extension project Popular University Vale do Gurguéia, at the Federal University of Piauí. Since the emergence of the extension in the university, there has been a relationship of hegemony and hierarchy of knowledge produced at university in relation to the knowledge experienced in the communities. In this relationship of knowledge, the university extension constitutes as one of the main elements for the dissemination of academic knowledge to society, but it can also be influenced by colonial narratives and oppressive power systems, affirmed by a paradigm of europeanized science. Historically, this paradigm has given notoriety and validity to knowledge considered superior to the knowledge produced in other contexts, aspect potentiated, above all, by the process of domination and subordination through colonization. Such domination expressed in peasant of knowledge has triggered resistance to the overcoming of this paradigm from the culture and knowledge of the South, especially Latin America, in a philosophical perspective decolonial and decolonical. The aim of this study is to identify and value the alternative pedagogical approaches of the popular extension and popular education that promote the decolonization of the university extension through the Popular Extension and educational practices of popular education, evidenced by potentialities and challenges, in its process of promoting a resignification of the extensionist practices university, through the overcoming of the hegemonic paradigm of extension, by the construction of a decolonial perspective, within and outside the academic space. The study was linked to the research line of Popular Education, in which its methodological process was guided by a qualitative approach, of the type research-action, which was carried out, a review of the literature, in addition to, documentary research, by means of video published on YouTube with testimonies and reports of scholars involved in initiatives of popular extension and popular education, in the experiences and experiences accumulated in the project of extension Popular University Vale do Gurguéia, at the Federal University of Piauí. For the analysis of the researched materials and data collected was adopted the hermeneutic-dialectical method, where the construction of the theoretical reference was based on the epistemological productions of authors and authors of the Popular Extension, Popular Education, the pedagogies and philosophy of Latin America and the University Extension. The expected result was the explicitation of a set of pedagogical practices and strategies that can be used and adapted for the university extension where it seeks to resignify also the relations between university and community in a way that builds a valuation of the popular knowledge and knowledge in the production of knowledge from the South of the World.